Resenha de KACZYNSKI, T. J. Technological Slavery. Vol. 1. Revised and expanded edition. Scottsdale: Fitch & Maddison, 2019. - Gabriel Garmendia da Trindade (Revista Opinião Filosófica)
Resenha de KACZYNSKI, T. J. Technological Slavery. Vol. 1. Revised and expanded edition. Scottsdale: Fitch & Maddison, 2019.